PENGARUH MOTIVASI TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP DI RSU SEMBIRING DELITUA TAHUN 2019 - Sentosa Barus (Jurnal Inovasi Kesehatan Masyarakat, 2020)
The primary role is to manage the implementation of health care such as training programs, trainers and participate in program activities are responsible. In other words, health care workers assigned as managing existing activities. Lack of motivation and retraining or refresher training for employees of the health department and the lack of guidance led to a lack of ability of public health officials in performing their duties. This resulted in an inaccuracy in the execution of his duty personnel. Therefore, it needs to be researched "The Effect Of Motivation On The Performance Of Employees In Sembiring Hospital District 2019.” This study uses descriptive analytic survey with cross sectional approach. Population as well as samples in this study were all employees of Sembiring Hospital District in 2019 with the number of employees 133 people. Processing and analysis of data is done by univariate, bivariates. The results of chi square analysis showed that there is an influence between the variables of achievement, respect, responsibility, supervision, working conditions, payment and safety, and policies with the employee performance where p value less than 0.05. While variable work itself does not affect the performance. Suggested to the leader of the health department, to give more attention in terms of creating a healthy working environment, apply the same policy that applies to all employees and also give rewards to employees who show the best performance. Based on the findings and limitations in this research, ongoing research needs to be done using a variety of other conditional factors.